STUDI PENINGKATAN EMPLOYEE ENGAGEMENT MELALUI PERSEPSI DUKUNGAN ORGANISASI DAN COUNTER PRODUCTIVE WORK BEHAVIOR DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. INTERNATIONAL FORTUNA EKSPRESINDO - kundori, kundori; kusdibyo, kusdibyo (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
This study was conducted to examine the effect of perceptual variables on organizational support and counterproductive work behavior on employee engagement in improving employee performance at PT. International Fortuna Ekspresindo. The population in this study were employees of PT. International Fortuna Ekspresindo. The analysis technique used is Structural Equation Modeling (SEM), where SEM is to test whether the model described in the study is in accordance with actual reality. Based on SEM results, it shows that perceptions of organizational support have a significant positive effect on employee engagement; perceived organizational support has a significant positive effect on employee performance; counterproductive work behavior has a significant positive effect on employee engagement; counterproductive work behavior has a significant positive effect on employee performance; and employee engagement has a significant positive effect on employee performance